Actividad antibacteriana de algunas especies medicinales de Eupatorium contra bacterias patógenas resistentes a antibióticos (POLIBOTÁNICA, 2017)
Thirty six samples arising from hexane, dichloromethane, and methanol extracts from four medicinal Eupatorium species were screened against Gram positive and Gram negative resistant bacteria associated with nosocomial infections by disk diffusion method. The best antibacterial extracts were selected by correspondence analysis. The hexane extracts showed high inhibition against clinical isolated bacteria. The qualitative chemical analysis was realized in the best antibacterial hexane extracts. The main components identified were triterpenes and benzopyran compounds which of extensively had been reported their antibacterial activities. Our results showing that medicinal Eupatorium species studied in this work have metabolites secondary antibacterial particularly against antibiotic resistant strains, Klebsiella pneumoniae and Staphylococcus aureus and validate their uses in traditional medicine